(3GdGfJUGQ Ydi YdeGA GdCeUGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3Yf GdfHi Udi Gddg Ydjg hSde , Cfg bdG (B:" (3dG hVhA EdG ef UhJ Ch QjM (B" (3ef HGH fhGbV GdhVhA s
(3BNQgG (B:s
(3jfJgi CKfGA HGH GdBPGf , Hbhdg (B: (3GdUaI GdKGdK MSf GdUhJ s
(3GdfSNI HgG MhGTs
(3LRA efIs
(3Ydi MhGTjgG JUMjMGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
Keywords: (3abg GdePGgH GdCNQis